Conectividad, hipermedialidad y multimodalidad: de la cultura digital al espacio escolar - Quintana Ramírez, Antonio (Colombian Applied Linguistics Journal, 2020)
This paper presents the main results achieved in the doctoral dissertation: “Hypertextuality and connectivity: alternatives of digital culture for the configuration of educative environments”. It focused on identify and describe the elements that characterize educational practices in educational environments in which connectivity, hypermediality and multimodality, along with the context of cyberculture, are promoted as central theoretical categories. The research corresponds to a micro-technographic study developed in IED, with a group of 30 students of 5th grade, in a specialized classroom equipped with tablets and full connectivity. The most important results and insights of the study are: 1) the emergence of the space of interaction as hypermedia itself; 2) a relationship between play and learning processes; 3) new dynamics of distributed attention; 4) symbolic distinction between the laboratory and the classroom; 5) to realize that pedagogical proposals are not as new as digital technologies; 6) due to its architecture, tablets do not help hypermedial writing; but multimodal writing and hybridization between digital and analogic technologies.